DAMPAK PENGEMBANGAN KARIER TERHADAP KEPUASAN KERJA KARYAWAN PADA PERUSAHAAN PT. ALAS KUSUMA KABUPATEN KUBU RAYA - Sarkawai, Yuana; Diana, Tri; Dewi, Andini Triana (Jurnal Ekonomi STIEP ( JES ), 2018)
Employee job satisfaction can be improved if there is justice in work. Achieving job satisfaction can improve productivity and company performance. Career development is an effort in increasing employee job satisfaction. The results show acceptance H0, proves that career development has no significant effect on employee job satisfaction. The career development orientation by companies that are not balanced with the expectations of employees cause employee job satisfaction is not going well.